Comparative Studies on Inhibitor Efficiency in Mild Steel and Iron - Rajkumar, D; Prasannan, D (International Journal of Engineering and Technology, 2018)
Metals generally corrode mild steel is an alloy form of from which undergoes corrosion easily in acidic medium. The corrosion   products are formed when a metal give its electrons to the oxidizing substances, the organic compounds containing sulphur, nitrogen and oxygen are known to be effectiveness depends on the electron density at the functional groups. We need to reduce the corrosion of steel by adding inhibitor. Tensile strength of steel varies depends on the corrosion. Thus, the aim of this project is to determine the inhibitor efficiency of thiourea, urea, and hydroquinone for the corrosion of normal steel and iron in common HCL medium consists of different concentration of inhibitor.